The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1259/bjr.20150680
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of DTI findings with neurocognitive dysfunction in children with Type 1 diabetes mellitus

Abstract: Objective: To determine whether there were diffusion tensor imaging (DTI) changes in the brain among children with Type 1 diabetes mellitus (DM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
3
16
0
1
Order By: Relevance
“…Some recent studies showed lower AD and higher RD values in patients with hyperthyroidism, autoimmune diseases, and demyelinating diseases 9,10,23,24 . In our study, lower AD values of white matter pathways and basal ganglia may be associated with the disintegration of white matter tracts or axonal damage, despite its statistical insignificance after correction.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…Some recent studies showed lower AD and higher RD values in patients with hyperthyroidism, autoimmune diseases, and demyelinating diseases 9,10,23,24 . In our study, lower AD values of white matter pathways and basal ganglia may be associated with the disintegration of white matter tracts or axonal damage, despite its statistical insignificance after correction.…”
Section: Discussionsupporting
confidence: 44%
“…Decreased FA and increased MD values were presented in various neurodegenerative and neuropsychiatric disorders, such as autoimmune diseases, demyelinating disease, hypothyroidism, and diabetes mellitus 9–11,21,23,24 . It is well known that thyroid hormones regulate brain development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower axial diffusivity in the temporal and parietal regions in children with T1DM also reported in a previous study (35). Another DTI study found a negative correlation between the ADC values of the parietal white matter, and indicate that brain damage may have begun at the cellular level in the preliminary stage of T1DM and neurocognitive impairments can't be avoided (36). Meanwhile, one DTI study found the fractional anisotropy was decreased in posterior white matter tracts, which have high connectivity with lots of posterior cortical regions, including the cuneus, precuneus, fusiform, and posterior parietal cortical regions (37).…”
Section: Discussionsupporting
confidence: 60%